Variation of the volume and intensity of physical activity in the current planning of the training process in women’s mini-football - Guba V.P.; Pleshakov A.A.; Makeev P.V.; Zherebkin N.N. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine and prove the feasibility of varying the volume and intensity of physical activity in the current training plan for female athletes in futsal. Methods and structure of the study. The pedagogical experiment, in which 24 athletes took part, was carried out during 2022/2023. on the basis of the MosPolitech mini-football club (Moscow), which takes part in the Russian championship among women’s teams. The principle scheme for the distribution of sports loads in the annual training cycle of athletes provided for a gradual increase in volume in the preparatory period (November - January), which stabilized in the competitive period (January - March), after which it constantly decreases. Results and conclusions. The volume and intensity of physical activity in the current training plan for qualified female athletes in the preparatory period of the annual training cycle tends to gradually increase, reaching its maximum towards its end. At the same time, it is characteristic that it is considered very advisable to dose physical activity in the preparatory period of the annual training cycle, taking into account the individual characteristics of qualified athletes in mini-football and their playing role, ensuring an increase in the level of physical and technical-tactical readiness.